The need for international reserves and credit facilities - Beaufort Wijnholds, J. A. H. de. (Leiden: Nijhoff, 1977)
This book deals with the problem of international liquidity with a particular reference to international monetary economics and international reserves and credit facilities.
Includes index.
Bibliography: p. 237-248.
usc 7/9/17
Loans
Keywords: International liquidity; International finance; Foreign exchange reserves; Economics